2016
DOI: 10.3415/vcot-15-02-0025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pelvic rotation on the standard hip ventrodorsal extended radiographic view

Abstract: The IHD is the recommended variable and OFW is an acceptable variable in order to evaluate slight pelvic rotation. The data may be used in qualitative analyses of hip extended radiographic views. In the future, complementary studies should be performed to evaluate the impact of degree of pelvic rotation on the hip dysplasia score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…In this study using a cadaveric model, the normal VDHE view showed a very low mean IHD asymmetry (less than 1°), similar to a previous study (Martins et al 2016) and the mean NA did not show statistically significant changes with pelvis rotation (2° to 6°), either on the dependent or nondependent side, which is not in agreement with some other studies (Genevois et al 2007;Skurkova et al 2010). In fact, the NA showed a consistent tendency to increase on the non-dependent side and greater degrees of rotation may result in statistically significant NA differences.…”
Section: Original Papersupporting
confidence: 90%
See 4 more Smart Citations
“…In this study using a cadaveric model, the normal VDHE view showed a very low mean IHD asymmetry (less than 1°), similar to a previous study (Martins et al 2016) and the mean NA did not show statistically significant changes with pelvis rotation (2° to 6°), either on the dependent or nondependent side, which is not in agreement with some other studies (Genevois et al 2007;Skurkova et al 2010). In fact, the NA showed a consistent tendency to increase on the non-dependent side and greater degrees of rotation may result in statistically significant NA differences.…”
Section: Original Papersupporting
confidence: 90%
“…Therefore, proper positioning and optimal exposure technique are essential prerequisites for radiographs of sufficient diagnostic quality to allow accurate HD assessment (Genevois et al 2007;Thompson et al 2007;Bausman and Wendelburg 2010). Pelvic rotation over the longitudinal axis changes hip radiographic morphology (Genevois et al 2007;Volta et al 2013;Martins et al 2016). Previously published works have reported the relationship between pelvis rotation and the projected DAE and NA on the dependent side and non-dependent side (Genevois et al 2007;Skurkova et al 2010), although not always with a sound scientific basis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations